INFERTILITY AND THE CHRISTIAN ATTITUDES TO ASSISTED REPRODUCTIVE TECHNOLOGIES (ARTS) IN NIGERIA: A Psychological Investigation - David Oluwabukunmi Ogunbiyi (QUAERENS: Journal of Theology and Christianity Studies, 2026)
Infertility, defined as the inability to conceive after at least one year of regular, unprotected sexual intercourse, remains a major psychosocial and spiritual issue in Nigeria, particularly among Christian couples. This study investigates the psychological and religious dimensions of infertility and examines Christian attitudes toward Assisted Reproductive Technologies (ARTs) such as in vitro fertilisation (IVF), intracytoplasmic sperm injection (ICSI), and surrogacy. Using a descriptive survey design, data were collected from 2,572 participants across various Christian denominations in Nigeria. Findings revealed that while awareness of ARTs is high, many Christians still struggle to reconcile their faith with the medical interventions these technologies represent. Anxiety, depression, and social stigma were common among infertile couples, particularly women, who often face cultural blame. Denominational doctrines significantly influence couples’ perceptions of ART morality and divine will. However, most respondents believe churches should support couples using ARTs. The study underscores the need for integrating psychological counselling and pastoral care into fertility treatment. It advocates a balanced approach that recognises ARTs as compatible with faith when pursued with informed conscience and emotional support. This integration enhances resilience, reduces stigma, and promotes holistic well-being for couples in faith-based communities.